Cultura de segurança do paciente em duas unidades de saúde do município de Vitória-ES - Paulo, Najla Gomes Nagib (2023)
Objective: Analyze the patient safety culture in two health units (US) in the Municipality of Vitória –ES. Methods: This is a cross-sectional study carried out in two Health Units in the city of Vitória-ES, being a basic health unit (UBS) and a family health unit (USF), using the Medical Office Survey on Patient questionnaire. Safety Culture (MOSPSC), prepared by the Agency for Healthcare and Research in Quality. Results: The overall MOSPSC composite percentage positive score was 51%. The positive patient safety culture was observed in four dimensions: Issues related to patient safety and quality (70%), Exchange of information with other institutions (71%), Teamwork (67%) and Monitoring of patient care (63%). Eight dimensions were classified as weaknesses that require interventions to improve the patient safety culture in the health units surveyed, with the one with the lowest percentage being Pressure and pace of work (19%). Conclusion: The evaluation of CSP in the two US researched showed weaknesses in patient safety, and it is important to plan training for health professionals aimed at safe care, promote the review of work processes and thus contribute to discussion and decision-making decision on appropriate management and risk management in the primary care context. This highlights the importance of strengthening discussions about patient safety in PHC.